2009
DOI: 10.1128/jcm.00342-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Real-Time PCR and Conventional Biochemical Methods for Identification of Staphylococcus lugdunensis

Abstract: Staphylococcus lugdunensis is an aggressive, virulent member of the coagulase-negative staphylococci (CoNS) that is responsible for severe, rapidly progressive skin and soft tissue infections and native valve endocarditis. To facilitate prompt identification and appropriate therapy, we describe here a rapid and robust multiplex real-time PCR assay that is able to definitively distinguish S. lugdunensis from other staphylococci. Using melting curve analysis, the assay also identifies Staphylococcus aureus and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…As outlined above, β-lactam allergy evaluation should be conducted in every case in which vancomycin is considered for use because poorer outcomes related to vancomycin therapy for a variety of MSSA infections are well recognized. 147 Clindamycin has been associated with IE relapse and is not recommended. 157 For MSSA IE in patients with anaphylactoid-type β-lactam allergy who exhibit either a suboptimal response to vancomycin or vancomycin allergy, β-lactam desensitization should be considered as noted above.…”
Section: Therapy Of Mssa Ie In Patients Allergic To or Intolerant Of mentioning
confidence: 99%
“…As outlined above, β-lactam allergy evaluation should be conducted in every case in which vancomycin is considered for use because poorer outcomes related to vancomycin therapy for a variety of MSSA infections are well recognized. 147 Clindamycin has been associated with IE relapse and is not recommended. 157 For MSSA IE in patients with anaphylactoid-type β-lactam allergy who exhibit either a suboptimal response to vancomycin or vancomycin allergy, β-lactam desensitization should be considered as noted above.…”
Section: Therapy Of Mssa Ie In Patients Allergic To or Intolerant Of mentioning
confidence: 99%
“…In the laboratory, CoNS may be misidentified. Pinsky et al reported that biochemical identification was only 31% sensitive and 77% specific for Staphylococcus lugdunensis when tested against PCR-based method (Pinsky et al, 2009). With increasing access to molecular and mass-spectrometry techniques, an increasing number of CoNS recovered from blood cultures and other sterile body sites are being correctly identified to the species level (Chen et al, 2013;Ho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding S. lugdunensis identification, despite its biochemical peculiarities, the reliability of these systems is too low and the accuracy of identification ranges from 70% to 90% depending on the system used and the performance of additional tests (7,8). In an effort to improve the identification rate, various molecular methods, particularly real-time PCR assays targeting some conserved genes such as gyrA, gap, sodA, and rpoB or 16S and 23S ribosomal DNA, have been successfully proposed (6,9,10). Identification by nucleic acid-based approaches appears to be a gold standard for S. lugdunensis, but the implementation of proteomic methods, particularly MALDI-TOF MS, in routine clinical laboratories has allowed a rapid, cost-effective, and reliable identification of bacteria, including staphylococci (2).…”
Section: S Lugdunensis Identification and Microbiological Issues Havmentioning
confidence: 99%